Mathematical modeling and calculation of interaction of boundary layer with traces of bodies of various form - Мамчук, В. І.; Мовчан, В. Т.; Шквар, Є. О. (Proceedings of National Aviation University (archive), 1999)
Given are the results of mathematical modeling of interaction of boundary layer on flat surface and traces of bodies of various form (streamlined and badly streamlined). Calculations are made in accordance with proposed and worked out residual difference method. The design parameters are compared to the well-known experimental data of E.G. Tylapyrkara, V. Ramzhy, R. Radzhasekara